Hydrodynamics of ship propellers - Breslin, John P.; Andersen, Poul 1951- (Cambridge ocean technology series, 1996)
Deals with flows over propellers and the hydrodynamic forces and moments which the propeller generates on the shaft and on the ship hull. The first part of the book is devoted to fundamentals of uniform flow. The second part covers unsteady section and blade forces arising from operation in non-uniform hull wakes.